Prevalence of Bourbon and Heartland viruses in field collected ticks at an environmental field station in St. Louis County, Missouri, USA - Ishmael D. Aziati; Derek McFarland Jnr; Avan Antia; Astha Joshi; Anahi Aviles-Gamboa; Preston Lee; Houda Harastani; David Wang; Solny A. Adalsteinsson; Adrianus C.M. Boon (Ticks and Tick-Borne Diseases, 2023)
Heartland and Bourbon viruses are pathogenic tick-borne viruses putatively transmitted by Amblyomma americanum, an abundant tick species in Missouri. To assess the prevalence of these viruses in ticks, we collected 2778 ticks from eight sampling sites at Tyson Research Center, an environmental field station within St. Louis County and close to the City of St. Louis, from May - July in 2019 and 2021. Ticks were pooled according to life stage and sex, grouped by year and sampling site to create 355 pools and screened by RT-qPCR for Bourbon and Heartland viruses. Overall, 14 (3.9%) and 27 (7.6%) of the pools were positive for Bourbon virus and Heartland virus respectively. In 2019, 11 and 23 pools were positive for Bourbon and Heartland viruses respectively. These positives pools were of males, females and nymphs. In 2021, there were 4 virus positive pools out of which 3 were positive for both viruses and were comprised of females and nymphs. Five out of the 8 sampling sites were positive for at least one virus. This included a site that was positive for both viruses in both years. Detection of these viruses in an area close to a relatively large metropolis presents a greater public health threat than previously thought.